The Safety and Efficacy of Desmopressin in Patients With Intracranial Hemorrhage and a History of Alcohol Use. (June 2022) - Gunther, Michelle; Witenko, Corey J.; Prust, Morgan; Salerno, David; Berger, Karen
Background: Patients with a history of alcohol use disorder are at an increased risk of hematoma expansion following intracranial hemorrhage (ICH) due to the effects of alcohol on platelet aggregation. Desmopressin (DDAVP) improves platelet aggregation and may decrease hematoma expansion in patients with ICH. However, DDAVP may also increase the risk of hyponatremia and thrombotic events. Evidence is limited regarding the safety and efficacy of DDAVP in alcohol use (AU)-associated ICH. Methods: This was a retrospective chart review of adult patients with radiographic evidence of ICH and a confirmed or suspected history of alcohol use upon admission. Patients were categorized into groups based on DDAVP administration. Safety outcomes included hyponatremia (serum sodium <135 mEq/L or decrease in serum sodium of ≥ 5 mEq/L for patients with baseline sodium <135 mEq/L) within 24 hours of ICH and thrombotic events within 7 days of ICH. The primary efficacy outcome was the incidence of hematoma expansion, defined as any expansion of the hemorrhage noted on repeat imaging within 32 hours. Results: In total, 52 patients were included in the safety analysis (27 DDAVP and 25 non-DDAVP). Although hyponatremia was numerically higher in the DDAVP group, there was no significant difference between groups (19.2% vs 4.2%, P = 0.192). Thrombotic complications were similar between the DDAVP and non-DDAVP groups (11.1% vs. 8%, P = 1.0). Thirty-nine patients met criteria for hemostatic efficacy analysis. There was no difference in hematoma expansion between the DDAVP and non-DDAVP groups (23.1% vs 34.6%, P = 0.71) and these findings were consistent after adjusting for differences in baseline characteristics (OR 0.63, 95% CI 0.1-3.3). Conclusion: The administration of DDAVP was not associated with adverse safety events, but did not significantly reduce the incidence of hematoma expansion in patients with AU-associated ICH.